Obstacle Avoidance Path Planning of Space Redundant Manipulator Based on a Collision Detection Algorithm - Zhu, Zhanxia; Jing, Sa; Zhong, Jianfei; Wang, Mingming (Xibei Gongye Daxue Xuebao, 2020)
This paper focuses on the path planning of free-floating space redundant manipulator in an environment with obstacles. Firstly, based on the idea of spherical bounding volume and spatial superposition, the spatial occupying relationship between obstacles and manipulators is described in a simpler way. Then the relative position relationship between straight line segment and sphere is used to judge whether a collision between the manipulator and the obstacle. With the principle of forward kinematics, we use the joint parameterization method to transform the path planning problem into a parameter optimization problem with constraints. In this optimization problem, the objective function is a weighted optimization objective function, which includes two terms, the first term describes the base attitude disturbance and the second one is established according to the requirement of avoidance collision. The motion trajectories of the manipulator joints can be obtained by solving the optimization problem using the particle swarm optimization algorithm. We choose a 7-DOF space redundant manipulator for simulation study, and simulation results show the effectiveness of the proposed method, there is no collision between the manipulator and obstacles, and there is no disturbance on the base attitude. What's more, the trajectory of the joint is smooth, which can make the end-effector reach the desired pose with a high accuracy. 针对障碍环境中自由漂浮模式空间冗余机械臂的路径规划问题进行了研究。首先基于球形包围盒和空间叠加思想简化描述障碍物和机械臂的空间占位关系，采用直线段与球体之间相对位置关系判断是否碰撞的检测方法。然后从正向运动学出发，运用关节参数化方法，把路径规划问题变为带约束的参数优化问题，并考虑基座姿态扰动最小以及碰撞规避建立多项加权的目标函数，通过粒子群优化算法求解最优解，得到机械臂关节运动轨迹。最后以七自由度空间冗余机械臂为例进行仿真，结果表明该方法可以实现有效避障，同时基座姿态受扰很小，关节运动轨迹平滑，且机械臂末端也能够以较高精度达到期望位姿。